Assessment of Hidden Hearing Loss in Tinnitus patients with Normal hearing - Yomna Magdy Zoghba; Wessam Mostafa Essawy; Mona Ahmed Kotait; Afaf Ahmed Emara (The Egyptian Journal of Otolaryngology)
Abstract Background Hidden hearing loss (HHL) is an auditory condition that impacts auditory neurological processing and hearing sensitivity in individuals with normal hearing. This basic neuronal degeneration doesn't influence hearing thresholds but likely adds to difficulties in comprehending speech in challenging auditory settings and might have a significant impact in the onset of tinnitus and/or hyperacusis. Objectives This work was performed to diagnose the existence of HHL and cochlear synaptopathy in individuals having tinnitus with normal hearing utilizing electrophysiological and physiological tests. Method This work involved two groups. The control group included 25 normal-hearing individuals. The study group involved 25 individuals having tinnitus with normal hearing. Hearing level was assessed by pure tone audiometry with extended high frequency. The TEN test assessed dead regions. The severity of tinnitus had been assessed using the Tinnitus Handicap Inventory Questionnaire (THI). Cochlear and auditory nerve functioning were assessed using distortion product otoacoustic emissions, click-evoked auditory brain stem response (ABR), and electrocochleography (EchoG). Results Results revealed a statistically significant difference in PTA threshold at standard audiometric frequencies, extended high frequencies (10–16 kHz), DPOEAs (DP & SNR) in certain frequencies, ABR (wave I amplitude), and AP amplitude in EchoG. 20% of participants in the study group showed an SP/AP ratio in EchoG of more than 0.4, possibly due to HHL presence. TEN test results did not indicate any threshold shifts. Therefore, no dead regions had been detected in both groups. Positive correlations were observed between the severity of tinnitus and PTA results across all frequencies, including extended high frequencies, PTA average, speech reception thresholds (SRT), distortion product (DP) at 3, 4, and 7, and SNR at 1, 6, and 8. A positive correlation existed between wave I amplitude and patient age. Age and tinnitus duration were positively correlated with THI scores. Conclusion Our results suggest that even if the hearing threshold is normal in standard audiometric frequencies in tinnitus patients, they may have HHL (cochlear synaptopathy).